Pengaruh Variabel Makroekonomi dan Variabel Spesifik Bank Terhadap Non Performing Financing Pada Bank Umum Syariah dan Unit Usaha Syariah di Indonesia Periode 2013-2014 - Daisy Firmansari; Noven Suprayogi (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research attempt to analyze the effect of variable gross domestic product (GDP), inflation and financing to deposit ratio (FDR) to non performing financing (NPF) of Islamic Commercial Bank and Islamic Business Unit in Indonesia. This research using quantitative methods. The study is based on quarterly data for the period 2003-2014. Typed of data used are the secondary data from official website Indonesian Bank and Bureau Statistic Center. The analytical methods used in this study is the method of multiple linear regression with a significance level of 0,05.The result of this research indicate that gross domestic product and inflation partially provide a significant influence to non performing financing. Only financing to deposit ratio have an insignificant influence to non performing financing. However, gross domestic product, inflation and financing to deposit ratio simultaneously provide a signification effect to non performing financing.